MENGENAL PANDAN BUAH MERAH DAN MANFAATNYA - Afrizal Malik; Anggi Sahru Romdon (JASEP, 2022)
Red fruit (Pandanus conoideus Lamk) is a species of the Pandanaceae tribe that has many uses, including as a source of raw materials for degenerative drugs such as heart, liver, cholesterol, diabetes, gout, osteoporosis, and anti-HIV infections. red can be used as animal feed. The genetic potential of red fruit in its natural habitat is not known with certainty. Besides red fruit, other wild pandanus species were also found, namely the pandan tree with small short fruit (20-30 cm) with a fruit circumference of 20 cm and 3 buds. The pandanus is not used as food because of its bitter taste. At an altitude of 1,000 m asl too found other types of pandanus similar to pandanus mats around the forest. The number of ethnic groups living in the Papua region also influences the naming of each red fruit plant accession. Meanwhile, it is known that there are 6 accessions that farmers in Papua are interested in/cultivated, namely Melar, Barugum, Ibagaya, Kuanggo, Kanen, and Muni. The processing method that is currently developing is generally still traditional. There is a need for wider development of red fruit, both plant propagation (eg by tissue culture) and processing methods.Keywords: red fruit, pandanus, traditional medicine